Pengetahuan dengan Sikap Penanganan Dismenore Pada Remaja Putri - Ahmad Aswad; Juwita Suma; Nurul Nadya Supono (Journal Nursing Care Jurusan Keperawatan Politeknik Kesehatan Gorontalo, 2021)
In some woman who experience menstruation, there will be pain during the menstruation. A knowledge influences handling menstrual pain. The more a person’s knowledge increases, the more effective it will be in handling menstrual pain.The study was conducted to find out the relationship of knowledge with an attitude of handling dysmenorrhea on adolescent girls at SMPN 1 Suwawa.This a quantitative descriptive research by using study sectional cross approach. The Independent variable is knowledge of dysmenorrheal,and the dependent variable is an attitude of handling dysmenorrhea.The population of this study is the adolescent girls or students of class VIII SMPN 1 Suwawa.There are 73 students as the sample which is selected by using total sampling technique. Univariate and bivariate then analyze the data.Research finding:based on the analysis result using chi-square test, it shows the X2  value is 4,933, because of the X2 value <0,05 where the significance level α= 5%, so the H0 is rejected.Conclusion: there was a significant relationship between the level of knowledge with the attitude of handling dysmenorrheal on adolescent girls at SMPN 1 Suwawa